Harnessing Zakat to Drive Inclusive Economic Growth: Prospects and Challenges - Fajri, Moh Najikhul; Kusumawardhani, Andini (UI Scholars Hub, 2025)
This study aims to analyze the role of zakat in promoting local inclusive economic growth in Indonesia. This research uses secondary panel data of 34 provinces during 2017-2022. The analysis techniques used in this study include the Poverty Equivalent Growth Rate (PEGR) inclusive economic growth measurement method and the Static Panel Regression Fixed Effect Model. This study concludes that zakat is proven to be an effective instrument in promoting inclusive economic growth in Indonesia, with a significant impact on income distribution even though its potential is still not optimized. Unique findings reveal that inclusive growth recovered faster than GDP post-pandemic, and Eastern Indonesia region showed better progress than Java as the economic center, indicating the existence of growth-versus-equity paradox.